Cardiorespiratory fitness, cognition and brain structure after TIA or minor ischemic stroke. Issue 7 (October 2017) - Boss, H Myrthe; Van Schaik, Sander M; Witkamp, Theo D; Geerlings, Mirjam I; Weinstein, Henry C; Van den Berg-Vos, Renske M
Background: It is not known whether cardiorespiratory fitness is associated with better cognitive performance and brain structure in patients with a TIA or minor ischemic stroke. Aims: To examine the association between cardiorespiratory fitness, cognition and brain structure in patients with a TIA and minor stroke. Methods: The study population consisted of patients with a TIA or minor stroke with a baseline measurement of the peak oxygen consumption, a MRI scan of brain and neuropsychological assessment. Composite z-scores were calculated for the cognitive domains attention, memory and executive functioning. White matter hyperintensities, microbleeds and lacunes were rated visually. The mean apparent diffusion coefficient was measured in regions of interest in frontal and occipital white matter and in the centrum semiovale as a marker of white matter structure. Normalized brain volumes were estimated by use of Statistical Parametric Mapping. Results: In 84 included patients, linear regression analysis adjusted for age, sex and education showed that a higher peak oxygen consumption was associated with higher cognitive z-scores, a larger grey matter volume (B = 0.15 (95% CI 0.05; 0.26)) and a lower mean apparent diffusion coefficient (B = −.004 (95% CI −.007; −.001)). We found no association between the peak oxygen consumption and severe white matter hyperintensities, microbleeds, lacunes and total brain volume. Conclusions: These data suggest that cardiorespiratory fitness is associated with better cognitive performance, greater grey matter volume and greater integrity of the white matter in patients with a TIA or minor ischemic stroke. Further prospective trials are necessary to define the effect of cardiorespiratory fitness on cognition and brain structure in patients with TIA or minor stroke.